2004
DOI: 10.1122/1.1764823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long branches on the rheology of polypropylene

Abstract: In order to study the rheology of long chain branched polymers, branches have been added on linear polypropylene precursors in varying amounts using reactive modification with peroxydicarbonates. The branched polypropylene samples show distinct strain hardening, something absent from the linear melt; this considerably improves the melt strength of the modified polymer. The zero shear viscosity and the elasticity measured by the relaxation spectrum also increase with the number of branches per molecule. Two mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 35 publications
4
122
1
1
Order By: Relevance
“…Münstedt et al provided excellent work on this topic [152,156,157] among other works. [128,130,158,159] However, the strain hardening in extension can also be a result of very small amount of high-molecular-weight materials in linear polymers. [160,161] The technique is not very sensitive to LCBD either.…”
Section: Extension Rheology (Strain-harding Effect)mentioning
confidence: 99%
“…Münstedt et al provided excellent work on this topic [152,156,157] among other works. [128,130,158,159] However, the strain hardening in extension can also be a result of very small amount of high-molecular-weight materials in linear polymers. [160,161] The technique is not very sensitive to LCBD either.…”
Section: Extension Rheology (Strain-harding Effect)mentioning
confidence: 99%
“…The best quantitative way to estimate the improvement of processing properties due to the addition of LCB on the linear chain is by directly measuring the strain hardening of the viscosity of the melt in uniaxial elongational flow, g þ E ð; _ Þ [30,31]. Indeed, in a series of peroxide-modified polypropylenes with increasing degree of long chain branches, Gotsis et al [30] showed that both the onset and the extent of strain hardening increased with B n .…”
Section: Measuring the Level Of Lcbmentioning
confidence: 99%
“…Indeed, in a series of peroxide-modified polypropylenes with increasing degree of long chain branches, Gotsis et al [30] showed that both the onset and the extent of strain hardening increased with B n . The whole g þ E ðÞ curves could be described well by classical viscoelastic models that implemented a damping function with a parameter, b, which reflected the level of LCB in the fluid.…”
Section: Measuring the Level Of Lcbmentioning
confidence: 99%
“…The activation energy for viscous flow is affected by chain flexibility, intermolecular interactions, the concentration of polar groups, and side-chain branches. While the presence of LCB yields an increase in both the temperature dependence and E a , the thermorheological behavior becomes complex [Malmberg et al (2002); Lohse et al (2002); Gotsis et al (2004)]. That is, the sequence of the molecular relaxations is temperature dependent.…”
Section: Introductionmentioning
confidence: 99%